2017
DOI: 10.1051/0004-6361/201630061
|View full text |Cite
|
Sign up to set email alerts
|

Searching for intermediate-mass black holes in galaxies with low-luminosity AGN: a multiple-method approach

Abstract: Aims. This work is the first stage of a campaign to search for intermediate-mass black holes (IMBHs) in low-luminosity active galactic nuclei (LLAGN) and dwarf galaxies. An additional and equally important aim of this pilot study is to investigate the consistency between the predictions of several popular black hole scaling relations and the fundamental plane (FP) of black-hole activity (FP-BH). Methods. We used well established X-ray and radio luminosity relations in accreting black holes, along with the late… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 139 publications
1
24
0
Order By: Relevance
“…large uncertainties on the Eddington ratio could also explain the high accretion rate of this source. The detection of jet radio emission spatially coincident with hard X-ray emission has been often used to estimate the BH mass by means of the fundamental plane of accreting BHs (e.g., Reines et al 2011Reines et al , 2014Mezcua & Lobanov 2011;Webb et al 2012;Hlavacek-Larrondo et al 2012;Koliopanos et al 2017;Mezcua et al 2013aMezcua et al ,b, 2015Mezcua et al , 2018, which is a correlation between nuclear X-ray luminosity, core radio luminosity, and BH mass valid from stellar-mass BHs to SMBHs in the hard X-ray spectral state (e.g., Falcke et al 2004). Several correlations with different scatters exist based on different samples with varied properties: e.g., the correlation from Merloni et al (2003) has the largest scatter (0.88 dex) as it includes both flat and steep radio sources, different accretion rates, and BH masses estimated using different methods; Gültekin et al (2009) use only dynamical BH masses and nuclear radio sources, which reduces the scatter to 0.77 dex; Plotkin et al (2012) include only sub-Eddington accreting sources and a Bayesian approach, which yields a scatter of 0.07 dex (see e.g., Mezcua et al 2018 for a brief review).…”
Section: Radio Emissionmentioning
confidence: 99%
“…large uncertainties on the Eddington ratio could also explain the high accretion rate of this source. The detection of jet radio emission spatially coincident with hard X-ray emission has been often used to estimate the BH mass by means of the fundamental plane of accreting BHs (e.g., Reines et al 2011Reines et al , 2014Mezcua & Lobanov 2011;Webb et al 2012;Hlavacek-Larrondo et al 2012;Koliopanos et al 2017;Mezcua et al 2013aMezcua et al ,b, 2015Mezcua et al , 2018, which is a correlation between nuclear X-ray luminosity, core radio luminosity, and BH mass valid from stellar-mass BHs to SMBHs in the hard X-ray spectral state (e.g., Falcke et al 2004). Several correlations with different scatters exist based on different samples with varied properties: e.g., the correlation from Merloni et al (2003) has the largest scatter (0.88 dex) as it includes both flat and steep radio sources, different accretion rates, and BH masses estimated using different methods; Gültekin et al (2009) use only dynamical BH masses and nuclear radio sources, which reduces the scatter to 0.77 dex; Plotkin et al (2012) include only sub-Eddington accreting sources and a Bayesian approach, which yields a scatter of 0.07 dex (see e.g., Mezcua et al 2018 for a brief review).…”
Section: Radio Emissionmentioning
confidence: 99%
“…While the formation channel of IMBHs is unknown, there are a small number of proposed scenarios: (i) the direct collapse of massive first-generation, lowmetallicity Population III stars [57][58][59][60], (ii) runaway mergers of massive main sequence stars in dense stellar clusters [61][62][63][64][65], (iii) the accretion of residual gas onto stellar-mass black holes [66], and (iv) chemically homogeneous evolution [67]. 6 It has been suggested that the most likely locations to find IMBHs are at the centers of GCs [68][69][70][71][72][73][74][75][76][77][78][79][80]. It follows that these are also the most likely places to find IMBHBs.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Each of these scaling relations may reveal possible candidates in the IMBH regime, however there are still large uncertainties in their estimations and the question of their validity in the low mass regime still remains. Nevertheless, in a recent publication [147] four independent mass scaling relations and the fundamental plane of black hole activity (FP-BH: see next paragraph) were combined to measure the mass of the central MBH in seven LLAGN that had previously been reported to host IMBHs [128]. While the study did not confirm the previous estimations (the MBHs had a log M BH /M ⊙ ≈6.5 on average), it demonstrated that all five (largely independent) methods produce consistent results in the low-mass regime.…”
Section: Central Imbhs: Black Hole Mass -Host Bulge Scaling Relationsmentioning
confidence: 99%
“…While the X-ray and radio observations and the FP-BH can reveal IMBH candidates (e.g. [171,147]), the scaling relation suffers from very high intrinsic scatter, therefore an estimation using solely the FP-BH would be very tentative. Nevertheless, as was demonstrated in Koliopanos et al [147] it can provide a crucial, independent verification of estimations carried out using other methods.…”
Section: Imbhs In Agn: the Fundamental Plane Of Black Hole Activitymentioning
confidence: 99%